레진계 치아 스플린팅 재료들의 중합능력 평가 - 이정길(Jeong-Gil Lee); 김수연(Soo-Yeon Kim); 이재관(Jae-Kwan Lee); 김진우(Jin-Woo Kim); 박세희(Se-Hee Park); 조경모(Kyung-Mo Cho) (Journal of dental rehabilitation and applied science, 2018)
Purpose: The aim of this study was to evaluate the polymerization ability of resin-based materials used for teeth splinting according to the thickness of cure. Materials and Methods: For this study, the Light-Fix and G-FIX developed for resinous splinting materials and the G-aenial Universal Flo, the high-flowable composite resin available as restorative and splinting material, were used. Ten specimens of the thickness of 2, 3, 4 and 5 mm and 5 mm in diameter for each composite resin (total 120) were prepared. The microhardness of top and bottom surfaces for each specimen was measured by the Vickers hardness testing machine. The polymerization ability of the composite resin for each thickness was statistically analyzed using independent T-test at a 0.05 level of significance. Results: There was no difference of polymerization ability regardless of the thickness in the Light-Fix and G-FIX. The G-aenial Universal Flo showed significantly low polymerization ability from the thickness of the 3 mm (P < 0.05). Conclusion: The Light-Fix and G-FIX, which are resin-based materials used for teeth splinting, are expected to be suitable for light curing up to 5 mm in thickness. 목적: 본 연구의 목적은 치아 스플린팅에 사용되는 레진계 재료들의 두께에 따른 중합 능력을 평가하는 것이다. 연구 재료 및 방법: 레진계 스플린팅 재료로 개발된 Light-Fix와 G-FIX, 수복용과 스플린트용으로 사용 가능한 고흐름성 복합레진인 G-aenial Universal Flo를 사용하여 직경 5 mm, 두께 2, 3, 4, 5 mm의 시편을 각각 10개씩(총 120개) 제작하였다. 비커스 경도 측정기를 이용하여 시편 상면과 하면의 미세경도값을 측정하였다. 각 두께에서 복합레진의 중합정도를 95% 유의수준에서 independent T-test를 이용하여 통계적으로 분석하였다. 결과: Light-Fix와 G-FIX는 두께에 상관없이 중합도의 차이를 보이지 않았다. G-aenial Universal Flo는 3 mm 두께부터 유의하게 낮은 중합도를 보였다. 결론: 스플린팅 전용 레진계 재료인 Light-Fix와 G-FIX는 5 mm 두께까지 적절한 광중합이 가능할 것으로 사료된다.